Synthesis and Characterization of Lanthanide(III) Nitrate Complexes with Terdentate ONO Donor Hydrazone Derived from 2-Benzimidazolyl Mercaptoaceto Hydrazide and o-Hydroxy Aromatic Aldehyde - Vinayak M. Naik; Nirmalkumar B. Mallur (E-Journal of Chemistry)
A few eight coordinated complexes of lanthanide(III) nitrate with 2-benzimidazolyl mercaptoaceto hydrazone ligand (LH2) with the general formula [Ln(LH)2NO2]H2O (where Ln = La, Pr, Nd, Sm and Gd) have been synthesized and characterized by elemental analysis, magnetic susceptibility, molar conductance, UV-Visible, IR and 1H NMR spectral studies. The experimental data sustain stoichiometry of 1:2 (metal/ligand) for the complexes. The spectral data shows that the ligand reacts in keto form and behaves as monobasic terdentate in nature. The nitrate appears to coordinate in the bidentate fashion to the metal ion. The thermal stabilities of the complexes have been studied by TGA and their kinetic parameters were calculated using Coats-Redfern and MKN methods. The antimicrobial activity studies have been under taken and results are discussed.